PENGEMBANGAN INSTRUMEN TES UNTUK MENGUKUR KEMAMPUAN KONSENTRASI BELAJAR BIOLOGI - Jamilah, Jamilah - (INSTITUT AGAMA ISLAM NEGERI AMBON, 2022)
Learning concentration is one of the indicators that can make it easier for students to achieve their learning goals. It is necessary to develop an instrument to detect the ability to concentrate on learning biology. This study aimed to develop a valid instrument for measuring the ability to study biology concentration. This type of research is the type of research used in research and development (research and development) with a 4-D development model consisting of 4 main stages, namely: (1) define, (2) design, (3) develop, and (4) disseminate. Based on the results and research findings, the developed biology learning concentration test is in the